2021
DOI: 10.1016/j.jacc.2021.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular Myocardial Fibrosis and Sudden Death in Patients With Brugada Syndrome

Abstract: Background Electrophysiological, imaging, and pathological studies have reported the presence of subtle structural abnormalities in hearts from patients with Brugada syndrome (BrS). However, data concerning disease involvement outside of the right ventricular outflow tract are limited. Objectives This study sought to characterize the presence and distribution of ventricular myocardial fibrosis in a cohort of decedents experiencing sudden cardiac death caused by BrS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 34 publications
0
28
1
Order By: Relevance
“…Together, these data suggested that in BrS, at the epicardial surface, interstitial fibrosis and reduced gap junction expression in the RVOT could lead to electrical anomalies. In further support of this finding, in 28 hearts from SCD cases with a non-confirmed diagnosis of BrS, the ventricular myocardium exhibited a higher proportion of collagen, irrespective of sampling location or myocardial layer (the highest proportion was found in the RVOT epicardium in individuals with suspected BrS) ( Table 1 ) [ 22 ]. There was no statistically significant association reported between SCN5A genotype and histotype.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Together, these data suggested that in BrS, at the epicardial surface, interstitial fibrosis and reduced gap junction expression in the RVOT could lead to electrical anomalies. In further support of this finding, in 28 hearts from SCD cases with a non-confirmed diagnosis of BrS, the ventricular myocardium exhibited a higher proportion of collagen, irrespective of sampling location or myocardial layer (the highest proportion was found in the RVOT epicardium in individuals with suspected BrS) ( Table 1 ) [ 22 ]. There was no statistically significant association reported between SCN5A genotype and histotype.…”
Section: Resultsmentioning
confidence: 86%
“…Other cases diagnosed with BrS but without a positive SCN5A genetic diagnosis could be due to other genetic alterations in this gene [ 35 ] or in other genes [ 36 ]. However, it is also important to remark that only in 57 cases reported in the three most recent studies [ 22 , 25 , 26 ], a comprehensive genetic analysis including gene encoding cardiomyopathies were performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathomechanism observed in BrS patients involves depolarization and repolarization abnormalities, inflammation of myocytes, and fibrosis in RVOT and/or RV [ 9 , 12 ]. A recent study performed on whole hearts from deceased patients, whose SCD was accounted to BrS, showed biventricular myocardial fibrosis, especially in the epicardium of the RVOT [ 17 ]. RV myocardium in a number of patients with BrS type 1 ECG pattern have showed histological changes comparable to arrhythmogenic RV cardiomyopathy (ARVC), and indicate possible autoimmune causes of myocardial inflammation in BrS patients [ 9 ].…”
Section: Pathogenesis Of Brsmentioning
confidence: 99%
“…There was a correlation between structural abnormalities and abnormal potentials, and their ablation abolished the BrS phenotype and malignant arrhythmias [ 9 ]. Another group confirmed that BrS is associated with increased collagen content throughout the RV and the LV, but irrespective of sampling location or myocardial layer in patients experiencing sudden cardiac death [ 61 ]. Based on the data provided above, an endomyocardial biopsy could become a new diagnostic tool for the research of concealed morphological abnormalities in BrS, as well as for the identification of dynamic arrhythmogenic substrates [ 75 , 81 , 82 ].…”
Section: Histopathological Findingsmentioning
confidence: 99%